Effect of thermal processing and mixing time on textural and sensory properties of stick chewing gum. (October 2019) - Saberi, Farzad; Azmoon, Elahe; Nouri, Mehran
Graphical abstract: Highlights: The temperature and duration of mixing effect on the textural and sensory quality of chewing gum. TPA parameters were significantly altered under different mixing conditions. Textural parameters of chewing gum, before and after chewing, are affected due to mixing conditions. Volatile compounds of chewing gum flavor are influenced under different mixing conditions. Abstract: This study examined the effect of mixing temperature (50 °C and 65 °C) and mixing time (5, 15, 25 and 35 min), as two major mechanical conditions in the mixing procedure of chewing-gum paste, on the textural and sensory properties of final stick gums. The gums were evaluated using a texture analyzer, scanning electron microscopy (SEM) and sensory evaluation. The control sample was compared to eight different mixing conditions. It was shown that increases in the mixing time and mixing temperature resulted in worse values for all textural parameters except cohesiveness, due to the abnormal recrystallization of sorbitol as the bulking sweetener. Hardness increased more than 48 percent for the sample made using 35 min mixing at 65 °C, which is of great importance for the quality of chewing gum. Moreover, SEM images at 2000x and 8000x magnifications clearly confirmed the textural evaluations. Also, sensory properties were highly affected by high temperatures. Results showed that the closest treatment to the control sample was S4, which was produced using 15 min mixing at 65 °C.